DILATION MECHANISM OF SEISMIC-WAVE AMPLIFICATION - Engelbrecht J.K.; Khamidullin Y.N. (My University, 1989)
To understand the role of internal sources, it is useful to distinguish between large- and small-scale (in terms of deformation) fluctuations. The large-scale fluctuations appear to result directly from the release of thermal energy by various physical and chemical processes in the medium. The small-scale fluctuations are most logically attributed to negative fluctuations in the density of the medium in which the bonds between its individual elements are weakened. In the discussion below we shall confine ourselves to fluctuations of this type. In failure mechanics, small-scale density fluctuations are referred to as dilations. In its propagation, along a given ray, a seismic wave encounters numerous dilations. This is to be expected, since the situation corresponds to random fluctuation around certain average values of the parameters. In addition to this distribution, the real medium may contain regions of high activity where the character of the fluctuations changes greatly. But we shall confine our discussion to the case of a regular distribution of dilations in the medium, which may be treated as the model case.